Study on Concept of Marketing Strategy: A Comparative Analysis of Marketing Strategies and Service Quality in Specialized and Deposit Money Banks (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Banking system is characterized by internal and external competition. The upsurge of new banks created room for innovation and further market sharing. A proxy to determine the extent of competition is the intensity of marketing strategies adopted by these banks in recent times. The strategies utilized by Specialized and Deposit Money Banks have been a subject of inquiry on whether they are alike or not. This work against the identified gaps, therefore, compares the marketing strategies adopted by specialized and deposit money banks and as well examines the effect of service quality management on performance of these banks. Having analyzed the data, the study found out that there is an insignificant difference between the marketing strategies (promotion strategy, customer relationship management strategy and service quality) adopted by specialized and deposit money banks. Guided by the findings, the study recommended that new entrants going into banking and other financial institutions should stick to the various marketing strategies under the study with the most focus on service quality management